Performance of UV Reactor for Total Coliform Removal from High and Low Strength Landfill Leachates - Aziz, Hamidi Abdul; Abu Amr, Salem S.; Othman, Osama Mohammed (Journal of Environmental Science and Engineering Technology, 2019)
The levels of bacteria in landfill leachate is recently determined by researchers, as they may affect human health through pathogenic bacteria contaminations in surface and groundwater. The current study evaluated the effectiveness of ultra violet (UV) oxidation process for total coliform bacteria removal landfill high and low strength leachates in Pulau Pinang, Malaysia. The UV oxidation was applied as follow; leachate sample from Pulau Burung Landfill Site (PBLS) which has low total coliform content (200 MPN/100 m/L) and high organics (COD 1400-1600 mg/L), while the other used leachate sample from Ampang Jajar Landfill Site (AJLS) with high initial total coliform (>24 x 104 MPN/100 mL) and low organics (COD 130-300 mg/L). The UV contact time was varied between 2 and 5 min at 75 x 103 (mW-s/cm2) UV dosage. Highest removal (99.2%) in terms of Most Probable Number (MPN) was obtained for Total coliform from leachate with high initial total coliform and lower organic content, while 94% removal was attained for leachate with low initial total coliform and high organics content. The study revealed that UV is an efficient process for the removal of microorganisms from leachate with low dissolved and suspended organic and inorganic contents.